Emergent treatments for β-thalassemia and orphan drug legislations. Issue 11 (November 2022) - Costa, Enrico; Cappellini, Maria Domenica; Rivella, Stefano; Chilin, Adriana; Alessi, Eva; Riccaboni, Massimo; Leufkens, Hubert G.M.; Luzzatto, Lucio
Highlights: β-THAL is one of the most prevalent blood disorders in some regions of the world. However, given its prevalence, in the EU and the US it is classified as a rare disease. A wide array of therapeutic approaches has been developed over the past decades. β-THAL is a learning case on the potential global impact of Orphan Legislations. Gene therapy for β-THAL is promising, but scenarios for global access are missing. Abstract : In many countries, β-thalassemia (β-THAL) is not uncommon; however, it qualifies as a rare disease in the US and in European Union (EU), where thalassemia drugs are eligible for Orphan Drug Designation (ODD). In this paper, we evaluate all 28 ODDs for β-THAL granted since 2001 in the US and the EU: of these, ten have since been discontinued, twelve are pending, and six have become licensed drugs available for clinical use. The prime mover for these advances has been the increasing depth of understanding of the pathophysiology of β-THAL; at the same time, and even though only one-fifth of β-THAL ODDs have become licensed drugs, the ODD legislation has clearly contributed substantially to the development of improved treatments for β-THAL.